On the identity of Adelophryne pachydactyla Hoogmoed, Borges, and Cascon, 1994 (Brachycephaloidea: Eleutherodactylidae) - Dominato, Ramon C.; Cassini, Carla S.; Silva, Janisete G.; Orrico, Victor G. D. (Zootaxa, 2018)
The use of molecular data for documenting biodiversity has become more common over time as larger datasets can be generated faster. Nevertheless, studies addressing phenotypical data have not become as common. As a collateral effect, many samples used in molecular studies are assigned to a species without checking phenomic characters of the vouchers. Correct specific assignment is paramount for any biological hypothesis. A recent review of Phyzelaphryninae, while producing interesting results, has not specified how some vouchers used in molecular analyses were assigned to each species. Using new sequences from fresh material collected in Southern Bahia, we re-identify Adelophryne specimens based on molecular and morphological grounds. This new taxonomic understanding clarifies the phylogenetic position of A. pachydactyla and highlights a more parsimonious explanation for the evolution of a morphological character—the reduction of a phalange on Finger IV—within Adelophryne.